Alabama - Thompson, Kathleen (Milwaukee, Wis. : Raintree Publishers, 1988)
Discusses the history, economy, culture, and future of Alabama. Also includes a state chronology, statistics, and maps.
"A Turner book."
"A Turner Educational Services, Inc. book. Based on the Portrait of American television series created by R.E. (Ted) Turner"--P. [2].
Includes index.
4.6
5-8
Keywords: Alabama -- Juvenile literature; Alabama; Alabama